2020
DOI: 10.3390/atmos11070741
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Biological Risk Assessment: Review of Existing and Description of a Comprehensive Approach

Abstract: Biological risks potentially affect workers in multiple occupational sectors through their exposure to pathogenic agents. These risks must be carefully assessed to prevent adverse health effects. This article identifies and critically analyzes approaches that manage the qualitative evaluation of biological risk (EvBR) as part of occupational health and safety prevention, for which no standard method yet exists. Bibliographic and computing references were searched to identify qualitative EvBR approaches, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Occupational risk is a common phenomenon among healthcare professionals [ 1 ]. While most of the previous studies have concentrated on the risk assessment of doctors and nurses, who were directly involved in patient care [ 25 ], fewer studies have focused on laboratory staff.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational risk is a common phenomenon among healthcare professionals [ 1 ]. While most of the previous studies have concentrated on the risk assessment of doctors and nurses, who were directly involved in patient care [ 25 ], fewer studies have focused on laboratory staff.…”
Section: Discussionmentioning
confidence: 99%
“…Although close contacts are predominant means of transmission for respiratory viruses, their airborne spread requires attention. Its probability varies, depending on the source of infective aerosol (respiratory or fecal), on the pathogen's survival in the environment, and on environmental conditions [26,27].…”
Section: Prevention: Knowing and Controlling Environmental Pathwaysmentioning
confidence: 99%
“…HBV is said to be the most infectious occupational hazard seen among HCWs [5]. Burzoni et al reported that biological risk in the workplace is responsible for over 300,000 deaths per year worldwide [6]. This underlines the importance of increased awareness of the existence of these agents and the need for personal protection practices.…”
Section: Introductionmentioning
confidence: 99%